2016
DOI: 10.1007/s00013-016-0899-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of drift of the generalized Brownian motion process: an example for the analytic Feynman integral

Abstract: In the theory of the analytic Feynman integral, the integrand is a functional of the standard Brownian motion process. In this note, we present an example of a bounded functional which is not Feynman integrable. The bounded functionals discussed in this note are defined in sample paths of the generalized Brownian motion process.Mathematics Subject Classification. 28C20, 60J65, 46G12.1. Introduction. The purpose of this note is to illustrate an effect of drift of the generalized Brownian motion process (GBMP). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Thus a GBMP is determined by the continuous functions a(t) and b(t). The function space C a,b [0, T ], induced by GBMP, was introduced by Yeh [26,27] and was used extensively in [6,7,8,9,10,11,12,13,14]. The function space C a,b [0, T ] used in [6,7,8,9,10,11,12,13,14] can be considered as the space of sample paths of the GBMP.…”
Section: Introductionmentioning
confidence: 99%
“…Thus a GBMP is determined by the continuous functions a(t) and b(t). The function space C a,b [0, T ], induced by GBMP, was introduced by Yeh [26,27] and was used extensively in [6,7,8,9,10,11,12,13,14]. The function space C a,b [0, T ] used in [6,7,8,9,10,11,12,13,14] can be considered as the space of sample paths of the GBMP.…”
Section: Introductionmentioning
confidence: 99%
“…The (generalized) Paley-Wiener-Zygmund (PWZ) stochastic integrals on the (generalized) Wiener space have been used in various papers, in particular, concerning Feynman integration theories [1][2][3][4]. In particular, the PWZ integral is used in the definition of Cameron-Storvick's Banach algebra S of functions on 0 [0, ] which is the space of generalized Fourier-Stieltjes transforms of the C-valued and finite Borel measures on 2 [0, ] [1]. Johnson [4] showed that S is isometrically isomorphic to the Banach algebra of the Fresnel integrable functions given by Albeverio and Høegh-Krohn [5].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in [5,6,8], the authors introduced the FFTs on the very general function space C a,b [0, T ] (rather than the Wiener space C 0 [0, T ]), and studied their properties and related topics. The function space C a,b [0, T ], induced by a generalized Brownian motion process (GBMP), was introduced by Yeh [22,23] and was used extensively in [4,5,6,7,8,9].…”
mentioning
confidence: 99%
“…In particular, the relations such as (1.2) and (1.4) do not hold between the GFFT and the GCP on the function space C a,b [0, T ]. For some previous work on the GFFT and the GCP, see [7], and for a more detailed study of the effect of drift on the GBMP, see [4] and the references cited therein.…”
mentioning
confidence: 99%
See 1 more Smart Citation